Localization of a gene for autosomal dominant osteopetrosis (Albers-Schönberg disease) to chromosome 1p21. - Van Hul, W (1997)
Albers-Schönberg disease, the classical form of osteopetrosis, is an autosomal dominant condition with generalized increased skeletal density due to reduced bone resorption. Characteristic radiological findings are generalized osteosclerosis, with, most typically, end-plate sandwichlike thickening of the vertebrae (Rugger-Jersey spine) and the bone-within-bone (endobones) phenomenon. We studied an extended kindred with Albers-Schönberg disease and found linkage with several markers from chromosome 1p21. The Albers-Schönberg gene is located in a candidate region of approximately 8.5 cM flanked by markers D1S486 and D1S2792. A maximum LOD score (Z(max)) of 4.09 was obtained in multipoint analysis at loci D1S239/D1S248. Possible linkage of osteopetrosis to this chromosomal region was analyzed because the CSF-1 gene, which is mutated in the op/op mouse model for osteopetrosis, is located in 1p21. However, SSCP and mutation analysis in patients did not reveal any abnormality, which excludes the CSF-1 gene as the disease-causing gene. This was confirmed by refined physical mapping of the CSF-1 gene outside the candidate region for the Albers-Schönberg gene. The identification of the molecular defect underlying Albers-Schönberg disease will therefore be dependent on the isolation of other genes from an 8.5-cM candidate region on chromosome 1p21.